2020
DOI: 10.1016/j.heliyon.2020.e05616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage systems and tillage direction on soil hydrological properties and soil suspended particle concentration in arable land in Uganda

Abstract: The 2030 Agenda for Sustainable Development addressing the issues of environmental degradation has been challenged by human developments and activities. Crop production systems and technologies (e.g. soil tillage) are among the leading factors causing environmental degradation. In this study, the effect of soil tillage systems (i.e. no-tillage (NT); stubble-mulching (SM); deep tillage (DT); and conventional tillage (CT)) on surface runoff volume (SRV), suspended sediment concentration (SSC), infiltration rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…There is a synergetic relationship between LULC changes and CC with other factors causing impacts in our environment (Agyemang 2012 ; Vu et al 2014 ). Whereas LULC change can lead to loss of soils and nutrients from poor agricultural activities (Fatumah et al 2020 ), it is the CC that is responsible for transporting the sediments and nutrients to the receiving water bodies through river/stream flows, run-off, and shallow groundwater (Urama and Ozor 2010 ; Huong and Pathirana 2013 ). LULC changes and CC have been studied at global, regional, and national levels.…”
Section: Introductionmentioning
confidence: 99%
“…There is a synergetic relationship between LULC changes and CC with other factors causing impacts in our environment (Agyemang 2012 ; Vu et al 2014 ). Whereas LULC change can lead to loss of soils and nutrients from poor agricultural activities (Fatumah et al 2020 ), it is the CC that is responsible for transporting the sediments and nutrients to the receiving water bodies through river/stream flows, run-off, and shallow groundwater (Urama and Ozor 2010 ; Huong and Pathirana 2013 ). LULC changes and CC have been studied at global, regional, and national levels.…”
Section: Introductionmentioning
confidence: 99%
“…e higher moisture contents in no tillage and minimum tillage treatments with the lower layer in deep tillage is likely because of this phenomenon, a finding corroborated by Sharma et al [49] and Lui et al [62], although it is in contrast with those reported by Kurshid et al ( 2006), Khan et al [51] and Aikins and Afuakwa [19]. In comparison to conventional tillage systems, Filho et al [63] noticed an increase in soil moisture content under NT and MT systems. ere are two methods that can account for the protection of soil water provided by residue return in a conservation system.…”
Section: Discussionmentioning
confidence: 79%
“…It had strong correlations with most of the water quality parameters, with significant correlation with nitrate (Table 6). Its impacts on water quality emanate from different directions, including soil erosion, due to unsuitable tillage approaches, like soil excavation, with poor soil conservation measures, as pointed out by Guzha et al [104]; and Fatumah et al [105], and cultivation on steep slopes of Mt Elgon. Application of agro-chemicals, like fertilizers, herbicides, and plant growth boosters, which contain phosphorus, nitrogen, and potassium, are also major sources of the nutrients observed.…”
Section: Discussionmentioning
confidence: 99%